A better prognostic stratification for the 8th edition of the AJCC staging system of gastric cancer by incorporating pT4aN0M0 into stage IIIA. (June 2019) - Chen, Yongming; Zhang, Guanrong; Zhao, Baiwei; Huang, Chunyu; Ling, Yihong; Li, Yuanfang; Zhou, Zhiwei
Abstract: Introduction: The aim of this study was to analyze the prognosis of gastric cancer patients categorized as pT4aN0M0, pT1N3aM0/pT2N2M0/pT3N1M0 of stage IIB and stage IIIA and to compare the optimistic prognostic stratification between the AJCC 8th edition staging system and the AJCC modified 8th (m8th) edition staging system by incorporating pT4aN0M0 into stage IIIA. Material and methods: A total of 1770 patients who underwent gastrectomy were enrolled in this study. The homogeneity, the discriminatory ability, the monotonicity of the gradient assessments, and the discriminatory ability of the AJCC 8th and m8th edition staging systems were compared by using the likelihood ratio χ2 test, a linear trend χ2 test, the Akaike information criteria (AIC) and Bayesian information criterion (BIC) calculations, respectively. Results: For patients staged IIB, the 5-year survival rate of the patients categorized as pT4aN0M0 were significantly worse than that of the patients categorized as pT1N3aM0/pT2N2M0/pT3N1M0 (59.9% vs. 72.4%, P = 0.036). By contrast, the prognoses of the patients between the pT4aN0M0 category and those staged IIIA were analogous (59.9% vs. 61.5%, P = 0.693). Compared with the 8th edition system, the modified 8th edition staging system had a better homogeneity (higher likelihood ratio χ [2] score, 441.17 vs. 436.24), discriminatory ability, monotonicity of gradients (higher linear trend χ2 score, 436.78 vs. 416.15) and smaller AIC (10364.98 vs. 10369.91) and BIC values (10447.13 vs. 10452.06). Conclusions: The prognosis of pT4aN0M0 was poorer than those of pT1N3aM0, pT2N2M0, and pT3N1M0, which were staged IIB. There is a better prognostic stratification for the AJCC 8th edition staging system of gastric cancer by incorporating pT4aN0M0 into stage IIIA. Highlights: The prognosis of pT4aN0M0 was poorer than the others which were staged IIB. The prognoses of pT4aN0M0 and IIIA were analogous. It is better prognostic stratification by incorporating pT4aN0M0 into stage IIIA.